How does scavenger receptor B1 polymorphism (rs4238001) affect the progression of Hepatitis C patients with persistent viral responses? - Ozdogan, Osman; Altintas, Zuhal (Annals of Medical Research, 2021)
Aim: Scavenger receptor B1 (SR-B1) is an important glycoprotein that plays an important role in the entry of hepatitis C virus (HCV) to hepatocyte. SR-B1 also acts as a modulator in many situations, such as both the natural and adaptive immune system. The effects of HCV on entry to hepatocyte and response to treatment in SR-B1 mutations were investigated in many studies performed before. We aimed to investigate the effects of SR-B1 polymorphism on liver in patients with noncirrhotic HCV who received pegylated-interferon + ribavirin treatment and had persistent viral response (SVR). Material and Methods: We included naive, non-cirrhosis patients diagnosed with HCV in our clinic between 2008 and 2009. We monitored approximately 53 patients form whom we obtained SVR after treatment and followed up regularly for at least twice a year for ten years. We evaluated ultrasonography, laboratory parameters and calculated non-invasive fibrosis scores (APRI and FIB-4).Results: A total of 91% of patients were genotype 1b and 9% were genotype 1a. 2 patients developed cirrhosis in 4th and 6th year of their follow-up. One of these patients had Wild type SR-B1 rs4238001 (Gly2Ser) (GG) genotype and the other had heterozygous SR-B1 (GA) genotype. We detected no cirrhosis in none of the other 51 patients. We found improvement in APRI and FIB4 scores during follow-up in patients with both wild type and heterozygous SR-B1 genotype. It was more pronounced in the heterozygous SR-B1 group (pretreatment and 10th year values, respectively 0.82±0.65, 0.38±0.24 for APRI, 1.79±1.12, 1.31±0.65 for FIB-4) (p 0.05). Conclusion: The improvement of noninvasive fibrosis scores of SR-B1 mutations in non-cirrhotic HCV patients with SVR was more prominent in the group with heterozygous mutations. Although no difference was detected between SR-B1 mutations in terms of risk of cirrhosis progression and HCC development, larger studies are needed in this direction.
Keywords: Hepatitis C virus (HCV); scavenger receptor; sustained virologic response (SVR)